IoT-Based Smart Utility Control System - Khansa niazi; Waleed Ahmad; Muhammad Hassan Nadeem (NUML International Journal of Engineering and Computing)
In the 21st century, particularly in regions like Pakistan, critical challenges such as water scarcity, rising gas costs, and the severe effects of climate change have become increasingly urgent. To tackle these issues, numerous IoT-based systems are being developed globally to promote efficient resource management and sustainability.  However, many of the currently available IoT solutions, such as 1NCE's Smart Utilities Management, Semtech's LoRa® Technology for Smart Utilities, and Robustel's Utility Management Solutions, are often expensive. These systems require specialized and costly appliances for their functionality, making them less accessible to average users, especially in regions with limited resources [1].  In contrast, the IoT-based Smart Utility Control System offers a more affordable and accessible alternative. This system integrates seamlessly with a smartphone-based Android application, utilizing Firebase as its platform. By eliminating the need for expensive supportive appliances, it provides an efficient and cost-effective solution for managing utilities like water and energy. The system is designed to ensure convenience, promote resource conservation, and support households in addressing challenges related to resource scarcity and rising costs, particularly in economically vulnerable regions. With two key modules, our proposed solution addresses critical issues households in Pakistan and similar regions face. The first module wireless connectivity of water tanks focuses on water monitoring and control, offering real-time monitoring of water levels in main and supply tanks. In a country facing diminishing water resources, our system's ability to alert users to low water levels and remotely control water motors can help prevent wastage and ensure efficient water usage, thereby mitigating the effects of water scarcity. The second module monitors and controls the gas geyser for energy-efficient preheating and remote operation. Through the mobile app, users can adjust and schedule the operation of the geyser according to their preferences. This includes setting specific times for the geyser to switch on or off, optimizing energy usage, and ensuring hot water availability. By providing this level of control and flexibility, our system promotes energy efficiency and enhances user convenience and comfort.